2020
DOI: 10.1097/pts.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Problems Related to the Readability and Comprehensibility of Drug Packages and Labels: A Systematic Review

Abstract: The aim of the study was to evaluate the effectiveness of interventions designed to reduce problems with readability and comprehensibility in drug labels.Methods: A systematic review of observational and experimental studies was conducted using MEDLINE (via PubMed), Embase, and Scopus databases. Two independent reviewers selected articles and collected data about study design, interventions, and outcomes.Results: Of 1786 studies screened, 17 were included in this systematic review. The main findings were descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(117 reference statements)
0
6
0
2
Order By: Relevance
“…The concept of LASA drugs as potential sources of error was described almost 50 years ago 5. Since then, diverse studies have assessed strategies to minimise medication selection errors; however, they have produced conflicting evidence as to whether the use of TML is beneficial or not 8 12–14 25 26. Our study showed that the use of TML in syringe labels led to a lower error rate compared with the use of non-TML-coded labels under simulation conditions.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The concept of LASA drugs as potential sources of error was described almost 50 years ago 5. Since then, diverse studies have assessed strategies to minimise medication selection errors; however, they have produced conflicting evidence as to whether the use of TML is beneficial or not 8 12–14 25 26. Our study showed that the use of TML in syringe labels led to a lower error rate compared with the use of non-TML-coded labels under simulation conditions.…”
Section: Discussionmentioning
confidence: 68%
“…In 2001, the Food and Drug Administration of the USA (FDA) promoted the FDA Name Differentiation Project and recommended the evaluation of the use of TML 9. However, despite being recommended by several institutions such as the German Interdisciplinary Association for Intensive Care and Emergency Medicine,10 to date, the evidence on the use of TML remains unclear, in part conflicting and mostly based on conventional observation studies 8 11–14…”
Section: Introductionmentioning
confidence: 99%
“…The significance of these characteristics has been underscored in research on the subject. 41,42 For instance, in Switzerland, an investigation examined whether the use of standardized labels with Tall Man Lettering for identifying syringes could reduce error rates. 41 In an in-situ simulation conducted in a critical care scenario, 30 nurses were tasked with identifying medications from a set of syringes with similar drug names.…”
Section: Discussionmentioning
confidence: 99%
“…Las estrategias de mejoramiento de la seguridad en el uso de medicamentos en farmacias ambulatorias, requieren de la implementación de actividades de educación continua de todo el personal involucrado, en especial, de aquellos que están al final de la cadena de su manejo encargados de dispensarlos. Además, es necesario establecer protocolos de almacenamiento, registro, identificación especial de medicamentos LASA (incluso por parte de los fabricantes), dispensación y reconocimiento, reporte de los errores de medicación al Instituto Nacional de Vigilancia de Medicamentos y Alimentos (Invima) y búsqueda oportuna del paciente implicado para reducir el riesgo de que pueda causarle daño (18,19) para que la mayoría se queden en errores de tipo A, como ha estado ocurriendo en los últimos años con el programa de farmacovigilancia aquí analizado. Sin embargo, sigue siendo necesario desarrollar estrategias de manera intensiva, en especial, para mejorar la oportunidad del reporte de los errores y reducir aquellos que puedan llegar a afectar al paciente, con el fin de fortalecer el sistema de farmacovigilancia establecido por el Invima (20).…”
Section: Discussionunclassified